ANALISIS MODUL AJAR PENDIDIKAN AGAMA ISLAM BERBASIS TEKNOLOGI UNTUK MENDORONG MODERASI BERAGAMA DI MADRASAH TSANAWIYAH - Febrianto Hakeu; Mohamad Steven Alim; Adisti Viska Sari Djarumia; Avelya Deysi Ramadya; Feronika Lambari (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyse the technology-based Islamic Religious Education (PAI) teaching module encouraging religious moderation at Madrasah Tsanawiyah in North Gorontalo. This study uses a qualitative approach to collect data through observation, interviews, and analysis of teaching module documents used in several madrasah. The results show that technology-based teaching modules, which integrate multimedia applications, learning videos, and e-learning platforms, have great potential to increase student engagement and facilitate their understanding of religious moderation values, such as tolerance, inclusivity, and respect for differences. However, the study also found several challenges, including limited technological infrastructure and a lack of teacher competence to optimise technology. Therefore, it is necessary to increase support through training for teachers and the development of technological infrastructure in madrasas to maximise the effectiveness of technology-based teaching modules. The conclusion of this study emphasises that with the proper support, technology-based teaching modules can be an effective tool in shaping moderate attitudes among Madrasah Tsanawiyah students, thereby encouraging more robust religious moderation in their daily lives.